A new synonymy in East Asian Urostylididae (Hemiptera: Heteroptera) - Zhou, Yanyan; Rédei, Dávid (Zootaxa, 2018)
Urostylididae is a moderately species-rich family of phytophagous, mainly arboricolous pentatomoid true bugs (Hemiptera: Heteroptera) currently comprising 8 genera and 172 species (Rider et al. 2018). All described species occur in Asia, but undescribed taxa are present in Madagascar (P. Štys, pers. comm.). The present short paper was prompted by a recent contribution by Kim et al. (2018), who reviewed the species of the genus Urostylis Westwood, 1837, occurring in Korea, including the description of a purportedly new species, U. koreana Kim & Jung, 2018. The identity of the latter species is clarified below, with proposal of a new subjective synonymy.